GRAND EUROPEAN EXPRESSES - Behrend, George.
1 online resource (256 pages)
Keywords: Grand European Expresses (1962) examines the trains de luxe of the International Sleeping Car and European Express Trains Company, from the Orient Express of the 1880s to the car-sleepers of the 1960s. As modern-day sleeper services are being resurrected across European rail networks, this book looks at the complex organisation that was required to run their forbears, with sleeping cars with clean bedding and conductors and dining cars with food and drink were in the right place at the right time across many different nations, systems and time-zones.